Tradisi Meta’ua dalam Perspektif Geografi Budaya pada Masyarakat Buton Selatan - La Uning; Andrias Andrias; Rahmawati Nurkarima; La Ode Nursalam (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2026)
The Meta'ua tradition plays an important role in maintaining cultural identity, preserving local wisdom, and shaping the cultural landscape of the community amidst the current of modernization. The purpose of this study is to analyze the symbolic meaning and value of local wisdom in the Meta'ua tradition in the community of Nggulanggula Village, South Buton Regency, from a Cultural Geography perspective. This study uses qualitative methods with data collection techniques through observation and in-depth interviews. The results show that the Meta'ua tradition forms a distinctive cultural landscape through traditional processions, dances, symbols, and the use of spaces such as Baruga Binawakili and Galampa as centers of cultural activities. Community interaction with the environment is seen in the use of garden produce, livestock, and cempaka flowers as supporting elements of the tradition, as well as through social participation that emphasizes the value of mutual cooperation. Traditional symbols such as machetes, spears, shields, red and white sashes, and traditional clothing reflect identity and serve as a unifying force for the community. Although modernization brings some simple adjustments, the essential values ​​of tradition remain intact. Thus, the Meta'ua tradition not only functions as a traditional procession, but also as a cultural symbol, a means of preserving local wisdom, and strengthening the identity of the Siompu District community within the Cultural Geography.